Modeling and Simulation of Invasive Applications and Architectures - Roloff, Sascha; Hannig, Frank; Teich, Jürgen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book covers two main topics: First, novel fast and flexible simulation techniques for modern heterogeneous NoC-based multi-core architectures. These are implemented in the full-system simulator called InvadeSIM and designed to study the dynamic behavior of hundreds of parallel application programs running on such architectures while competing for resources. Second, a novel actor-oriented programming library called ActorX10, which allows to formally model parallel streaming applications by actor graphs and to analyze predictable execution behavior as part of so-called hybrid mapping approaches, which are used to guarantee real-time requirements of such applications at design time independent from dynamic workloads by a combination of static analysis and dynamic embedding.
Introduction -- Fundamentals -- InvadeSIM-A Simulation Framework for Invasive Parallel Programs and Architectures -- Hybrid Network-on-Chip Simulation -- Parallel MPSoC Simulation and Architecture Evaluation -- ActorX10 and Run-Time Application Embedding -- Conclusions and Future Directions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronic Circuits and Systems; Processor Architectures